2017
DOI: 10.1111/1440-1681.12806
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin overcomes acquired tamoxifen resistance through AIB1 and inhibits cancer cell invasion in endocrine resistant breast cancer

Abstract: Salinomycin is a monocarboxylic polyether ionophore isolated from Streptomyces albus. It has been widely used as an antibiotic in veterinary medicine in poultry. A recent study demonstrated that salinomycin selectively inhibits human breast cancer stem cells; one possible mechanism of tamoxifen resistance. Our results show that salinomycin is effective in inhibiting MCF-7/LCC2 and MCF-7/LCC9 cell lines which are well-established endocrine resistant cells and has a synergistic effect in combination with tamoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Meanwhile, some cell lines that were sensitive to Sal were not sensitive to the clinical commonly used drug cisplatin, including M29, SK-Mel-19, and A375 cell line (Supplementary Table S2 ). Some studies have indicated that Sal can specially damage tumor cells that are insensitive to drugs induced apoptosis, including drug resistant cancer cells 40 , 41 . Our study provided a new case to this field and showed that the mechanism of Sal was not limited to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, some cell lines that were sensitive to Sal were not sensitive to the clinical commonly used drug cisplatin, including M29, SK-Mel-19, and A375 cell line (Supplementary Table S2 ). Some studies have indicated that Sal can specially damage tumor cells that are insensitive to drugs induced apoptosis, including drug resistant cancer cells 40 , 41 . Our study provided a new case to this field and showed that the mechanism of Sal was not limited to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were incubated with primary antibody solution at 4 °C overnight after blocked, and then incubated with secondary antibody solution for an hour. Images were captured by densitometric scanning (Tanon-5500, Shanghai, China) and analyzed by ImageJ software 41 .…”
Section: Methodsmentioning
confidence: 99%
“…It seems that SI-2-based molecules are promising agents for specifically inhibiting SRC-3 in BCa, and we will probably discuss them further in the next few years. On the other hand, it was shown that salinomycin directly inhibits SRC-3 transcription and increases the sensitivity of BCa cells to tamoxifen [295]. Although salinomycin inhibits the malignant behaviors of BCa cells and kills CSCs, it isn't a specific SRC-3 inhibitor [296].…”
Section: Src-3 Is a Promising Target To Overcome Therapy Resistance I...mentioning
confidence: 99%
“…These findings suggest that GA could be used as a potential inhibitor of SRC-3 for cancer therapy. Salinomycin, an antibiotic, was found to down-regulate the transcription of SRC-3 and increase the sensitivity of breast cancer cells to tamoxifen treatment, which indicates salinomycin may be developed as SRC-3 inhibitor for endocrine-resistant breast cancer [ 157 ]. However, it has not been examined whether GA and salinomycin have an effect on the expression of SRC-1 and SRC-2.…”
Section: Src-3 As Therapeutic Targetmentioning
confidence: 99%